Optimising the grey water footprint of crops to enhance the environmental integrity in the Gaza Strip, Palestine - Amjad Mizyed; Yunes Mogheir; Mazen Hamada (Journal of Water and Land Development)
Water pollution and scarcity are amongst the most pressing challenges affecting the water environment in the Gaza Strip. Agricultural activities play an important role in this issue, consuming more than 50% of the extracted water, while contributing to environmental degradation through the excessive use of pesticides and fertilisers. The grey water footprint (GWF) was quantified to evaluate pollution from crops using the Hoekstra methodology. The grey water totalled 30.63 mln m3 , with 51% attributed to vegetables, 44.5% to horticultural trees, and 4.5% to field crops between 2018 and 2022. An evaluation of the sustainability of the water footprint revealed that the assimilation capacity of water resources has been completely consumed. As a result, the Gaza Strip is classified as an unsustainable area, which is a serious violation of globally approved water quality standards. To optimise the grey water footprint, the nitrogen balance, N-leakage rate, and associated uncertainties were analysed using fractional programming, leading to the development of a model aimed at achieving optimal results. The findings show the importance of implementing this approach in the Gaza Strip, enabling policymakers and local authorities to develop a promising strategy for agricultural practices. This would promote sustainable and effective management of water resources and a safe and productive agricultural environment.